2000
DOI: 10.1002/(sici)1097-0134(20000215)38:3<261::aid-prot3>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Water penetration and escape in proteins

Abstract: The kinetics of water penetration and escape in cytochrome c (cyt c) is studied by molecular dynamics (MD) simulations at various temperatures. Water molecules that penetrate the protein interior during the course of an MD simulation are identified by monitoring the number of water molecules in the first coordination shell (within 3.5 A) of each water molecule in the system. Water molecules in the interior of cyt c have 0-3 water molecules in their first hydration shell and this coordination number persists fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
142
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 44 publications
17
142
0
Order By: Relevance
“…Nevertheless, this description bears some limitations, and has to be reformulated for large cavities that accommodate major solvent clusters. 48,49 In this work, we trace solvent molecules involved in the interface between MHC and bound peptide by following the time-history of their coordination number. In this way, we can identify water penetration and escape events.…”
Section: Instantaneous Water Coordination Numbermentioning
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, this description bears some limitations, and has to be reformulated for large cavities that accommodate major solvent clusters. 48,49 In this work, we trace solvent molecules involved in the interface between MHC and bound peptide by following the time-history of their coordination number. In this way, we can identify water penetration and escape events.…”
Section: Instantaneous Water Coordination Numbermentioning
confidence: 53%
“…This number is obtained for every saved configuration by counting all water molecules within a range of 3.5 Å from the water oxygen atom, which defines the first hydration shell of water. 48 Water molecules in bulk have four to six water molecules in their first hydration shell. However, the instantaneous coordination number covers a range of 0 -12 coordinated neighbors per water molecule, having its peak in N c ¼ 5 for bulk water.…”
Section: Instantaneous Water Coordination Numbermentioning
confidence: 99%
“…Twenty-seven molecules stayed for at least 300 ps. 18,19 They have obtained similar, unpublished results for nuclease. (2) Our X-ray studies of nuclease show that welllocalized water molecules are often seen in the hydrophobic core in association with polar residues placed there by site-directed mutagenesis.…”
Section: Transiently Buried Water Moleculesmentioning
confidence: 99%
“…Firstly, the use of an implicit-solvent PMF ignores the time-dependent response of the solute surroundings, and we are assuming the reconfiguration of the solvent is fast relative to contact formation. 37 Secondly, we are assuming pairwise additivity in our potentials. Simulations of the association of three methane molecules in water have shown that the three-body PMF is not additive and requires an additional cooperative term.…”
Section: Resultsmentioning
confidence: 99%